Dynamic contact networks of swine movement in Manitoba, Canada: Characterization and implications for infectious disease spread. Issue 5 (22nd May 2019) - Augusta, Carolyn; Taylor, Graham W.; Deardon, Rob
Abstract: We use swine shipping data from Manitoba to construct one‐mode dynamic contact networks of swine locations and two‐mode location‐to‐truck networks at four time scales: daily, weekly, monthly and for the entire two‐year study period. We provide measures of graph evolution and graph characterization for each, useful in the development of statistical models related to infectious disease transmission. We find that Manitoba shipping practices differ from those in other Canadian regions, and particularly that truck sharing is more common in Manitoba than elsewhere in the country.